2019
DOI: 10.1158/1940-6207.capr-19-0244
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin Suppresses Patient-Derived Xenograft Tumor Growth by Directly Targeting AKT in Esophageal Squamous Cell Carcinoma

Abstract: Scutellarin is a flavonoid compound that is found in Scutellaria barbata. It has been reported to exhibit anticancer and anti-inflammation activities. However, the anticancer properties of scutellarin and its molecular targets have not been investigated in esophageal squamous cell carcinoma (ESCC). In the current study, we report that scutellarin is a potential AKT inhibitor that suppresses patient-derived xenograft ESCC tumor growth. To identify possible molecular targets of scutellarin, potential candidate p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Moreover, SCU affects RPMI7951 cell growth by regulating the phosphorylation levels of ERK1/2 and histone H3 in a time- and dose-dependent manner [ 114 ]. Kim et al [ 121 ] found that SCU was a potential AKT inhibitor that inhibits patient-derived xenograft ESCC tumor growth. Given that AKT can act as a substrate of TOPK, it would be worthwhile studying whether SCU affects the expression of AKT by targeting TOPK.…”
Section: Development Of Topk Inhibitors and Potential Compoundsmentioning
confidence: 99%
“…Moreover, SCU affects RPMI7951 cell growth by regulating the phosphorylation levels of ERK1/2 and histone H3 in a time- and dose-dependent manner [ 114 ]. Kim et al [ 121 ] found that SCU was a potential AKT inhibitor that inhibits patient-derived xenograft ESCC tumor growth. Given that AKT can act as a substrate of TOPK, it would be worthwhile studying whether SCU affects the expression of AKT by targeting TOPK.…”
Section: Development Of Topk Inhibitors and Potential Compoundsmentioning
confidence: 99%
“…The basic processes of IHC were followed [36]. Briefly, paraffin-embedded tissues (5 μm) were prepared for IHC analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Oridonin, Xanthohumol, and Scutellarin are natural compounds isolated from herbs. Their activities in targeting AKT activation in ESCC cells and ESCC-PDX have been reported [ 133 135 ]. These AKT inhibitors were effective in suppressing cell growth and inducing cell cycle arrest in ESCC cells as well as decreasing PDX tumor growth in vivo .…”
Section: Application Of Pdx Models In Evaluating Therapeutic Targets For Chemotherapymentioning
confidence: 99%
“…These AKT inhibitors were effective in suppressing cell growth and inducing cell cycle arrest in ESCC cells as well as decreasing PDX tumor growth in vivo . Importantly, the effects of these inhibitors were dependent on AKT protein level in ESCC cells [ 134 , 135 ].…”
Section: Application Of Pdx Models In Evaluating Therapeutic Targets For Chemotherapymentioning
confidence: 99%